2009
DOI: 10.1002/mc.20596
|View full text |Cite
|
Sign up to set email alerts
|

Up regulation of GW112 Gene by NFκB promotes an antiapoptotic property in gastric cancer cells

Abstract: To clarify the regulatory mechanism of GW112 gene expression, 5'-flanking region of the human GW112 gene was isolated and characterized in the present study. 5'-RACE analysis showed a single transcription start site, which is located 142 nucleotides upstream of the translation initiation site. Transient transfection studies with serial deletion constructs and close examination of the sequences identified a putative NF kappaB binding sequence between -442 and -430, which could be responsible for efficient expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 42 publications
3
52
1
Order By: Relevance
“…Functionally, OLFM4 has also been shown to behave as an antiapoptotic factor and to promote tumor growth and invasion (see Discussion;refs. 42,43). Confirming previous reports, we found that OLFM4 was indeed highly expressed in GCs compared with gastric normals (P < 0.001; Fig.…”
Section: Frequent Genomic Loss Of Mir-486 In Gcsupporting
confidence: 92%
See 2 more Smart Citations
“…Functionally, OLFM4 has also been shown to behave as an antiapoptotic factor and to promote tumor growth and invasion (see Discussion;refs. 42,43). Confirming previous reports, we found that OLFM4 was indeed highly expressed in GCs compared with gastric normals (P < 0.001; Fig.…”
Section: Frequent Genomic Loss Of Mir-486 In Gcsupporting
confidence: 92%
“…OLFM4 has been reported to be overexpressed in various cancers including GC but also colon, breast, and lung cancers (41), and has been proposed as a potential serum biomarker of GC (39). Functionally, OLFM4 has been shown to interact with GRIM19 (a cell-death regulatory protein), cadherins, and lectins, and OLFM4 has been shown to inhibit apoptosis and promote tumor growth and invasion (41)(42)(43). However, a recent finding showed that OLFM4 has a proapoptotic effect in myeloid leukemia cells (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, nothing is currently known about the role of distal enhancer elements in the regulation of Olfm4 expression. However, there are multiple transcription factor-binding sites in the proximal promoter important for Olfm4 expression, including nuclear factor-kB (NF-kB) (Huang et al 2010;Kim et al 2010b) and RBP-J, the main transcriptional mediator of Notch signaling (VanDussen et al 2012). In the DMR at the proximal promoter, CpGs are directly adjacent to the NFkB-and predicted RBP-J- binding sites.…”
Section: Dmrs (Supplementalmentioning
confidence: 99%
“…Both OLFM1 and OLFM4 have been implicated in apoptosis. Mutations in OLFM1 [28] and silencing of OLFM1 resulted in increased apoptosis [29]. OLFM4 may have differing roles depending on the tissue, being antiapoptotic in gastric cancers [30] and growth promoting in pancreas and lung cancer cells [31,21].…”
Section: Discussionmentioning
confidence: 99%